Ответы и объяснения

2014-02-21T16:49:39+00:00
Лучший Ответ!
2014-02-21T17:02:16+00:00
А1) а) y' = (2 e^{-x}+ x^{3})' = -2* e^{-x}+3 x^{2}
б) y' = ( 3^{x}+ \frac{3}{x})' =  3^{x}*ln3 -  \frac{3}{ x^{2} }
в) y' = (ln \frac{x}{2}- e^{x})' =  \frac{1}{ \frac{x}{2} } * \frac{1}{2}- e^{x}=  \frac{2}{x}* \frac{1}{2}- e^{x}=  \frac{1}{x}- e^{x}
г) y' = ( e^{3}-8* log_{5}x)' = 0-8* \frac{1}{xln5}=- \frac{8}{xln5}
A2) a) y' = ( 5^{x}+sinx)' =  5^{x}*ln5+cosx
б) y' = (-x* e^{2x})' = - e^{2x}-2x* e^{2x}
в) y' = ( 10^{x}+ e^{-x})' =  10^{x}*ln10- e^{-x}
A3) y = f (x₀) + f '(x₀) (x-x₀)
f '(x) = (4 e^{-x}-3)' = -4 e^{-x}
f '(x₀) = f '(0) = -4* e^{0}= -4
f (x₀) = f (0) = 4  e^{0}-3 = 4-3 = 1
y = 1 - 4(x-0) = 1-4x
B1) y' = (lnxsinx)' = (lnx)'*sinx + lnx * (sinx)' =  \frac{sinx}{x}+lnx*cosx
B2)  \int\limits^1_- { ( \frac{1}{2}) ^{x} } \, dx =  \frac{ ( \frac{1}{2}) ^{x} }{ln0.5} = \frac{ \frac{1}{2} }{ln0.5}- \frac{ ( \frac{1}{2}) ^{-1} }{ln0.5}=   \frac{1}{2ln0.5}- \frac{2}{ln0.5}= \frac{1-4}{2ln0.5}= - \frac{3}{2ln 2^{-1} }= -\frac{3}{-2ln2}= \frac{3}{ln4}